Pembangunan Perumahan Dengan Hunian Berimbang Bagi Pemenuhan Kebutuhan Rumah Untuk Masyarakat Berpenghasilan Rendah - Sri Maharani (Jurnal Penelitian Hukum Legalitas, 2015)
The house is a basic human need, therefore, the state must guarantee the fulfillment of the house, especially the urban poor. It has dimanatkan also in the Constitution 45 Article 28 H, and strengthened in Law No. 1 of 2011 on housing and settlement area as well as Law No. 20 of 2011 on the Flats. The method used in this research is empirical juridical, with the analysis of legislation related to legal theories as well as constraints-constraints faced. The study found that 1) the implementation of the balanced residential housing development to meet the needs of the common home for the MBR, it still has not done the maximum; and 2) The need for an increase in the underlying policy formulation balanced residential development with strategic, effective and implementable.